Imagining new feminist futures: How feminist social movements contest the neoliberalization of feminism in an increasingly corporate‐dominated world. Issue 8 (8th June 2018) - Grosser, Kate; McCarthy, Lauren
Abstract : Increasingly it is argued that feminism has been co‐opted by neoliberal agendas: becoming more individualistic and losing touch with its wider social change objectives. The neoliberalization of feminism is driven in part by increased corporate power, including the growing role of corporations in governance arenas, and corporate social responsibility agendas. However, we turn to social movement theory to elucidate strategies that social movements, including feminist social movements, are adopting in such spaces. In so doing, we find that feminist activists are engaging with new political opportunities, mobilizing structures and strategic framing processes that emerge in the context of increasingly neoliberal and privatized governance systems. We suggest that despite the significant challenges to their agendas, far from being co‐opted by neoliberalism, feminist social movements remain robust, existing alongside and developing new strategies to contest the neoliberalization of feminism in a variety of innovative ways.